ANALISA PERBEDAAN INFORMASI ANATOMI THORAKS PADA PROYEKSI ANTERO POSTERIOR (AP) SUPINE ANTARA PENYUDUTAN ARAH SUMBU SINAR 50 CAUDAD DAN VERTIKAL TEGAK LURUS - Nugroho Yudho Susilo; Bagus Abimanyu (JRI (Jurnal Radiografer Indonesia), 2018)
Backgroud: A finding about different central ray arrangement in the AP supine projection which are using 5° caudad and vertically central ray that occur in the clinical practice hospital turns into the reason of developing this research. A research has been carried out in the clinical practice hospital about thorax x - ray examination with AP supine projection that used 5° caudad and vertically central ray in order to reveal the anatomical information differences between thorax x-ray examination with AP supine projection with the variation of central ray angulation and also to determine the most effective degree of central ray which can demonstrate anatomical information accurately. Methods: The method of this research is quantitative with survey approachment, and qualitative approachment in addition. Data collected by copying 60 thorax x-ray radiograph, admission filling of questioner and interview. The questioner filled by 3 respondents who are radiologist. Those data from the respondents are processed and analysed by using statistical analysis. Results: Interviewing data analysed by data reduction, data presentation, drawing of conclusion and verification. Based on the result of the SPSS statistical Mann-Whitney analysis test, it has been revealed that there are differences of anatomical information between thorax x -ray examination with AP supine projection which are using 5° caudad and vertically central ray, demonstrated by magnification of clavicle, foreshortening of clavicle, foreshortening of costae’s distance, superposition of 1st-5th costae by clavicle, and superposition between anterior and superior co stae. It has been determined that vertically central ray radiograph can demonstrate anatomical information of thorax x - ray examination with AP supine projection accurately by the highest value of Mann -Whitney mean rank 44,68.